Geographical origin of chronic Chagas disease patients in Brazil impacts the performance of commercial tests for anti-T. cruzi IgG - Amadeo Sáez-Alquezar; Angela Cristina Verissimo Junqueira; Andressa da Matta Durans; André Valpassos Guimarães; José Abol Corrêa; José Borges-Pereira; Patrícia Lago Zauza; Pedro Hernan Cabello; Pedro Albajar-Viñas; David William Provance Jr; José Rodrigues Coura (Memorias do Instituto Oswaldo Cruz, 2021)
BACKGROUND Chagas disease, caused by Trypanosoma cruzi, affects nearly six million people worldwide. Various serological tests have been developed for its diagnosis. OBJECTIVE Examine the performance of a set of commercial immunological assays in relation to the geographical origin of the patient sample comparing four states of Brazil: Amazonas (AM), Mato Grosso do Sul (MS), Minas Gerais (MG) and Piauí (PI). METHODS Seven immunoassays were employed to detect anti-T. cruzi IgG antibodies in 379 patient samples that had been previously diagnosed using the two-step protocol required by the Brazilian Ministry of Health. FINDINGS A significant variation in the percent reactive was calculated for the samples from AM and MS, while the PI and MG showed a significant variation in the percent non-reactive. The average reactivity index was significantly higher for samples from the states of PI and MG states than AM and MS. MAIN CONCLUSIONS All tests presented a satisfactory performance overall. Yet, variations were observed that were associated to the region of origin of the samples. Our analyses suggest that future evaluations of immunoassays should include a sampling of sera from regions where the test will be applied in addition to the available International Biological Reference Standards.